Estilos de socialización parental y perfil psicológico en adolescentes según revisión documental (2020)
The study carried out an analysis of the parental socialization styles and psychological profile in adolescents according to a documentary review in Latin American research between the years 2014 to 2019, where studies were identified that allowed each category to be described according to the context and the problems that this implies. Based on the theoretical foundation proposed by Musitu, García, (2001), Papalia, Duskin, (2010) and Trejo, (2014), it was assumed that the relationships between the family context and the sociocultural environment endow the adolescent with a sufficient identity to think that these can positively or negatively influence their behavior. The type of research was qualitative, descriptive, under documentary review. The instrument that allowed the collection of bibliographic data which were framed in a digital file in which all the information found was interpreted. In conclusion, it was established that both categories become a complex phenomenon, which implies multidimensional circumstances such as social, political, economic, cultural, environmental, which revolve around one's own feelings capable of motivating and adjusting relationships with the environment. Among the recommendations made, government entities are required to dictate public policies that cover the multidimensionality of the behavior problems of adolescents, which not only affect the feelings and emotions of families but of the entire national conglomerate, against which They must take the pertinent actions to evaluate situations of vulnerability in adolescents in the family, community and school.